Catholic bioethics for a new millennium - Fisher, Anthony, 1960- (Cambridge, UK ; New York : Cambridge University Press, 2012)
"Can the Hippocratic and Judeo-Christian traditions be synthesized with contemporary thought about practical reason, virtue and community to provide real-life answers to the dilemmas of healthcare today? Bishop Anthony Fisher discusses conscience, relationships and law in relation to the modern-day controversies surrounding stem cell research, abortion, transplants, artificial feeding and euthanasia, using case studies to offer insight and illumination. What emerges is a reason-based bioethics for the twenty-first century; a bioethics that treats faith and reason with equal seriousness, that shows the relevance of ancient wisdom to the complexities of modern healthcare scenarios and that offers new suggestions for social policy and regulation. Philosophical argument is complemented by Catholic theology and analysis of social and biomedical trends, to make this an auspicious example of a new generation of Catholic bioethical writing which has relevance for people of all faiths and none"--
Machine generated contents note: Abbreviations; Preface; Introduction; Part I. How are we to do Bioethics?: Section 1. Context: Challenges and Resources of a New Millennium: 1. Sex and life in post-modernity; 2. Catholic engagement with the culture of modernity; 3. Promising developments; 4. Conclusion; Section 2. Conscience: The Crisis of Authority: 5. The voice of conscience; 6. The voice of the magisterium; 7. Conscience in post-modernity; 8. Where to from here?; Section 3. Cooperation: Should we ever Collaborate with Wrongdoing?: 9. Traditional example; 10. Five modern examples; 11. Some fundamental issues raised by these examples; 12. Why it matters so much; 13. Conclusion; Part II. Beginning-of-Life: Section 4. Beginnings: When do People Begin?: 14. Method, thesis and implications; 15. A closer look at Ford's science; 16. A closer look at Ford's philosophy; 17. Individuality criteria; 18. Conclusions; Section 5. Stem Cells: What's all the Fuss About?: 19. Scientific potential and concerns about stem cells; 20. Ethical concerns about embryonic stem cells; 21. Social concerns about embryonic stem cells; Section 6. Abortion -- and the New Eugenics: 22. The perennial debate about abortion; 23. Pre-natal screening: a search and destroy mission?; 24. The new abortion debate; Part III. Later Life: Section 7. Transplants: Bodies, Relationships and Ethics: 25. Love beyond death; 26. Conceptions of the body and relationships in organ transplantation; 27. Fashionable bioethical approaches to organ procurement; 28. Better bioethical approaches to organ procurement; 29. Ethical issues in organ reception; 30. Conclusion; Section 8. Artificial Nutrition: Why do Unresponsive Patients Matter?: 31. Civilisation after Schiavo?; 32. Why the unresponsive still matter: a philosophical account; 33. Why the unresponsive still matter: a theological account; 34. Some final questions; Section 9. Endings: Suicide and Euthanasia in the Bible: 35. The problem of suicide and euthanasia in the Bible; 36. Suicides and euthanasias in the Bible; 37. The Scriptural basis of Judeo-Christian opposition to suicide and euthanasia; Part IV. Protecting Life: Section 10. Identity: What Role for a Catholic Hospital?: 38. A tale of two hospitals; 39. Current challenges for Catholic hospitals; 40. Catholic hospitals as diakonia; 41. Catholic hospitals as martyria; 42. Catholic hospitals as leitourgia; 43. Conclusion: six tasks for a new century; Section 11. Regulation: What Kinds of Laws and Social Policies?: 44. A tale of three politicians; 45. Catholic principles for politicians; 46. Reasonable stances for a pro-life politician; 47. Some virtues of a pro-life politician.
Includes bibliographical references and index.
Keywords: Catholic Church -- Doctrines; Medical ethics -- Religious aspects -- Catholic Church; Bioethics -- Religious aspects -- Catholic Church